The Millerites and the Seven Trumpets of Revelation - Rodrigues, Gerson Cardoso (Revista Hermenêutica (descontinuada), 2014)
Abstract The purpose of this article is to present the Millerite’s growth, understanding and contribution on the interpretation of the seven trumpets of the book of Revelation. This research will be a documentary study based on published primary sources. Since many Millerites wrote articles and letters in which they mention their interpretation on the trumpets, it is above the scope of this research to comment on all of them. Therefore, the article will focus on William Miller (founder of the Millerite movement) and Josiah Litch (the “theologian” of the movement). Nevertheless, it does not exclude brief comments about other Millerites. Secondary sources will be used where appropriate to furnish information concerning historical context and background of perceptive insights. It is beyond the scope of this research, however, to either depict in detail the development of their interpretation or to analyze what was original from them and what they copied from contemporary expositors. Moreover, this research does not intend to examine every detail of the prophecy but only explore the dates and events they hold as the beginning and ending of the trumpets. Keyword: seven trumpets; Millerite; William Miller; Josiah Litch Resumo O objetivo deste artigo é apresentar o crescimento, entendimento e contribuição do movimento milerita sobre o tema das sete trombetas do livro do Apocalipse. Esta pesquisa será um estudo bibliográfico baseado em fontes primárias publicadas. Desde que muitos mileritas escreveram artigos e cartas nas quais eles mencionam suas interpretações sobre as trombetas, está além do objetivo deste estudo comentar sobre todos eles. Portanto, este artigo concentrará em William Miller (fundador do movimento milerita) e Josiah Litch (o “teólogo” do movimento). Entretanto, isto não exclui breves comentários sobre outros mileritas. As fontes secundárias serão utilizados sempre que necessário para fornecer informações sobre o contexto histórico. Está além do escopo desta pesquisa, no entanto, retratar em detalhes o desenvolvimento de sua interpretação ou analisar o que foi original deles e o que eles copiaram de expositores contemporâneos. Além disso, esta pesquisa não tem a intenção de examinar todos os detalhes da profecia, mas apenas explorar as datas e eventos que eles determinavam como o início e o final dos períodos das trombetas. Palavras-Chave: Sete trombetas; Mileritas; William Miller; Josiah Litch